Benefit of Nutrition Supplement with Vitamin D in Reducing the Risk of Myopia among Children - Chensie S. Angkasa; Rillya D. P. Manoppo; Wenny P. Supit (Universitas Sam Ratulangi, 2022)
Abstract: The cause of increased myopia worldwide is largely driven by environmental factors, especially lifestyle changes resulting from a combination of decreased outdoor time and increased work activities using devices, especially with close proximity. This study aimed to review the efficacy of providing nutritional supplementation with vitamin D in reducing the risk of myopia in children as an alternative to sunlight that should be obtained. This was a literature review study using several databases, namely, Pubmed, Clinical Key, Science Direct, and Google Scholar. The searching was carried out by entering the keywords Myopia, Myopia in Children, and Vitamin D.Â There were no significant results reported in several studies on the efficacy of vitamin D without the aid of sunlight as a means of activating vitamin D in the body. The efficacy of providing nutritional supplementation with vitamin D in an effort to reduce the risk of myopia in children will be maximized when given together with adequate sun exposure as a medium for converting the active form of vitamin D. Vitamin D supplement was more effective in early age of six years and not so significantly effective in teenagers. In conclusion, the benefit of nutrition supplement with vitamin D to decrease the risk of myopia in children is influenced by age and sun exposure.Keywords: myopia in children; vitamin DÂ Abstrak: Penyebab peningkatan miopia secara luas didorong oleh faktor lingkungan, terutama perubahan gaya hidup yang dihasilkan dari kombinasi penurunan waktu di luar rumah dan peningkatan aktivitas kerja menggunakan gawai terutama dengan jarak yang dekat. Penelitian ini bertujuan untuk mengetahui khasiat pemberian suplementasi nutrisi dengan vitamin D terhadap upaya penekanan risiko miopia pada anak sebagai alternatif dari sinar matahari yang mestinya didapatkan.Â Jenis penelitian ialah suatu literature review dengan pencarian data menggunakan beberapa database yaitu, Pubmed, Clinical Key, Science Direct, dan Google Scholar. Pencarian dilakukan dengan memasukan kata kunci Myopia, Myopia in Children, dan Vitamin D. Hasil yang tidak begitu bermakna didapatkan pada beberapa penelitian terhadap khasiat vitamin D tanpa dibantu sinar matahari yang menjadi sarana aktivasi vitamin D dalam tubuh. Khasiat pemberian suplementasi nutrisi dengan vitamin D dalam upaya menekan risiko miopia pada anak akan maksimal bila diberikan bersamaan dengan paparan sinar matahari yang cukup sebagai media pengubah bentuk aktif vitamin D. Pemberian suplemen vitamin D lebih efektif pada anak usia dini mulai dari 6 tahun dan tidak begitu bermakna pada anak berumur belasan tahun. Simpulan penelitian ini ialah khasiat pemberian suplemen nutrisi dengan vitamin D untuk menekan risiko miopia pada anak dipengaruhi oleh faktor usia dan paparan sinar matahari.Kata kunci: miopia pada anak; vitamin D